The Effect of Cooking Class on the Eating Behavior of Children Playing Groups in the Pesantren District of Kediri City - Devy, Novaria Hudawati; Jannah, Miftakhul; Masitoh, Siti (International Journal for Educational and Vocational Studies, 2019)
This study aims to examine the effect of cooking class on vegetable eating behavior in children. This research is quantitative approach with a quasi experimental research design with a non equivalent control group design. The total sample of 64 children were divided into two groups, namely the experimental and control groups. Data is collected through two stages, namely pretest and posttest. In the experimental group treatment was given in the form of cooking class while the control group did not. The treatment was carried out four times. Data collected by observation and documentation techniques. Indicators of vegetable eating behavior observed were consuming various vegetables, physical activity of children, drinking water. The types of vegetables used in this study were 6 types of vegetables that are close to children's daily life, namely tomatoes and leeks (group A vegetables), broccoli and carrots (group B vegetables), peas and soy bean sprouts (group C vegetables). Hypothesis testing uses the Anova test with the help of SPSS 25 for Windows Evaluation Version. The results showed that there were significant differences in vegetable eating behavior between the experimental and control groups.